Bacterial Inoculation and Extracts of Opuntia Rackets or Marine Algae Trigger Distinct Proline Balances in Tomato Salt Stress Alleviation - Abdelwahab Rai; Margarida M. Santana; Rodrigo Nascimento Maia; João Tavares; Elhafid Nabti; Cristina Cruz (Agronomy, 2023)
High salt levels in soil can severely limit plant development and diminish the positive effect of plant-growth-promoting rhizobacteria (PGPR). However, extracts of organisms adapted to high salinity, such as Opuntia ficus-indica (OFI) and Enteromorpha intestinalis (EI), can restore the growth of PGPR. Therefore, we used OFI or EI extracts and their combination with the PGPR Achromobacter xylosoxidans BOA4 to evaluate salt stress relief in tomato (Solanum lycopersicum). The experimental setup consisted of a plant pot trial under greenhouse conditions with 12 treatments: control, irrigation with OFI extract; EI extract; BOA4-inoculated plus OFI extract and BOA4-inoculated plus EI extract under no salinity or salinity conditions (150 mM NaCl). The percentage of germination, and plant’s fresh and dry weight were registered 30 and 46 days after sowing. At 46 days, the ratio between proline and glutamic acid concentration (PR/GA) was determined, expecting high PR/GA ratios in plants more responsive to salt stress since proline is an osmolyte mainly synthesized from glutamate. The results showed that 52% of the control seeds under salt stress germinated, a figure that was increased to 92% in OFI-treated seeds. Tomato plants were shown to be very sensitive to salt stress since the dry weight was ca. one fourth that of the plants grown without salinity. However, EI or BOA4 plus EI stimulated plant biomass by ca. 3 times compared to the control with salt, restoring plant biomass to values comparable to those of control plants grown without salinity. The joint treatments with BOA4 and EI or OFI caused distinct PR/GA levels in plant tissues. An inverse relationship between the sum of relative shoot proline and glutamic acid contents and shoot biomass accumulation was observed, namely in treatments accumulating more biomass under no salinity and salinity conditions. This indicates that the proline/glutamate pathway represents a carbon sink that is needed to fight stress and is competing with the carbon flow used for growth.